Posterior reversible encephalopathy syndrome during the peripartum period: report of four cases and review of the literature. - Buyukaslan, Hasan; Lok, Ugur; Gulacti, Umut; Sogut, Ozgur; Kaya, Halil; Gokdemir, Tahir; Yalin, Oner (My University, 2023)
Posterior reversible encephalopathy syndrome (PRES) is a cliniconeuroradiologic disorder affecting the brain's occipital and parietal lobes characterized by altered mental status, seizures, headache and blurred vision. Eclampsia is one of the main causes of posterior reversible encephalopathy. We aimed to discuss here literature guided clinical and radiologic findings of four women who had experienced status epilepticus at peripartum period and diagnosed as PRES.
Keywords: Posterior reversible encephalopathy syndrome; peripartum period; seizure